Iranian Biosafety Act (2009): Legal Gaps And Challenges - AMIR SAMAVATI PIROUZ; NASSRIN MEHRA (International Journal of Pharma and Bio Sciences, 2012)
Iranian Biosafety Act (2009) suffers from some shortcomings in legislative level and in criminal policy taken to approve it. The purpose of this article is to indicate what legal gaps in the Act are, which measures should be taken to protect environment and biosafety to the extent they deserve and why criminal responses stipulated in the Act are not severe and deterrent enough to protect environment. It seems that legal gaps in Iranian Biosafety Act (2009) have made the Act so unable that it neither can defend environment nor can it secure biosafety and biodiversity. In some cases, even the Act paves the way for non-professionals to abuse the environment under the pretext of implementing regulatory mechanisms. In this article, literature, Cartagena Protocol, criminal policy taken in stipulating crimes against biosafety with legal provisions and governing criminal policy will be studied and finally, some suggestions will be proposed. This writing may discourage those involved in the process of legislating Iranian Biosafety Act (2009) but the authors believe that the environment does deserve more criminal protection and it should be neither a target of offenders’ crimes, nor an issue ignored by Iranian legislator.